MOTIVATION ANALYSIS OF CROWDFUNDING DONATION BASED DISCLOSURE - Bestari, Ruli; Rahadian, Yan (Dinasti Publisher, 2020)
This study aimed to understand the degree of accountability related to disclosure of online donation crowdfunding report and provide some recommendation for adequate disclosure of crowdfunding online donation from stakeholder. This study is motivated by the fact that cyber scam of online donation increased and absence spesific regulation about donation crowdfunding from regulator to mitigate. Signaling theory and stakeholder theory are applied in this study. Two different approaches to asses motivation of online donation crowdfunding disclosure, such as the self enlightened interest consider as ethical business and genuine accountability as mandatory business. Kitabisa.com choosen as single unit analysis for this study. This study employ mixed method with content and thematic analysis processed by Nvivo 12 pro. It is found that self enlightened interest still dominant and play important role in Kitabisa.com disclosure report. Recommendations for disclosure from donors to answer where is their money go such as campaign detail description, publication or clarification, campaign detail financial report, time limit for disclose campaign report, recap or plan for funding utilization, interaction between donors and campaigner and add visual document to reduce assymetri information and strength stakeholder engagement